Analisis Faktor – Faktor Berpengaruh Pada Proses Treatment Pengolahan Limbah Minyak Mentah Pada PT. Wastec Internasional - Eko Wahyu Songgo Buwono; Mad Yusup; Diyaa Aaisyah Salmaa Putri Atmaja (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The research took place at Wastec Internasional Company, a company engaged in environmental waste processing services. The oil from the crude oil waste processing treatment process still has Basic Sediment and Water (BS&W) content and oil content that is too high so that it cannot reach the established standards so that the company must make efforts to reduce waste from the production process. The purpose of the study was to determine the sigma value, the number of defects and factors causing quality failure in crude oil processing treatment at PT Wastec Internasional. The methods used are the DMAIC method, control maps and fishbone diagrams. The calculation results obtained an average BS & W sigma value of 3.4 and an oil content sigma value of 3.29. The average number of defects for BS&W was 9.075% and for oil content was 2113 mg/L. The factors causing treatment quality failure are material, method and environmental factors.